ψ-Hilfer fractional relaxation-oscillation equation - Vieira, N. (2022)
In this work, we solve the ψ-Hilfer fractional relaxation-oscillation equation with a force term, where the time-fractional derivatives are in the ψ-Hilfer sense. The solution of the equation is presented in terms of bivariate Mittag-Leffler functions. An asymptotic analysis of the solution of the associated homogeneous equation is performed.